IDENTIFIKASI KESULITAN BELAJAR SISWA PADA OPERASI HITUNG BILANGAN DALAM MENYELESAIKAN SOAL CERITA SMPN 2 TANJUNG PALAS - Ardiansyah Ardiansyah; Hariaty Hamid; Alfian Mucti (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2019)
This study aims to find out how much percentage of each student's learning difficulties at number operations in solving the story problems in class VIII of Tanjung Palas State Middle School 2. This research was conducted in the odd semester of 2018/2019.This type of research is quantitative. The sampling technique used by Nonprobability Sampling with the type of Purposive Sampling sampling technique is the determination of samples with certain considerations, where the number of students sampled is 26 students. The results showed that the student learning difficulties with the highest percentage average score for students of Tanjung Palas 2 Public Middle School were operating indicators of 38.72% with a high category, followed by a principle of 43.59%, with a high category of concepts with categories 48.46% high, and 62.05% facts with a low category.